2011
DOI: 10.1002/dta.349
|View full text |Cite
|
Sign up to set email alerts
|

Phenazepam and cannabinomimetics sold as herbal highs in New Zealand

Abstract: A smokeable product called Kronic, is legally available, sold under five product names, and marketed in New Zealand as containing natural extracts. Two such products called Pineapple Express and Purple Haze were purchased from shops in Auckland city. They were investigated for the presence of synthetic drugs specifically synthesized for recreational purposes. The synthetic cannabinomimetics identified were JWH-018, JWH-073, JWH-122, JWH-250, and 1-pentyl-3-(4-methoxybenzoyl)indol. A compound not previously rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…It seems that there are two different groups of phenazepam users: those who take phenazepam as a part of a spectrum of sedatives and those who use phenazepam in an effort to manage the come-down effects of stimulant use. Since the analysis of seized samples has revealed mixtures of phenazepam and various different designer stimulants [21], and since phenazepam has also been found in mixtures with synthetic cannabinoids [22], some of the phenazepam positive individuals might even be unaware of the fact that they had taken phenazepam. Consequently, even if the drug taking pattern among users of phenazepam is as a rule multi-drug use, a person with an extremely high phenazepam blood concentration is likely to not have taken any of the so-called hard drugs like amphetamine or cocaine, but rather a mixture of sedatives with relatively low toxicity which are rarely fatal.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that there are two different groups of phenazepam users: those who take phenazepam as a part of a spectrum of sedatives and those who use phenazepam in an effort to manage the come-down effects of stimulant use. Since the analysis of seized samples has revealed mixtures of phenazepam and various different designer stimulants [21], and since phenazepam has also been found in mixtures with synthetic cannabinoids [22], some of the phenazepam positive individuals might even be unaware of the fact that they had taken phenazepam. Consequently, even if the drug taking pattern among users of phenazepam is as a rule multi-drug use, a person with an extremely high phenazepam blood concentration is likely to not have taken any of the so-called hard drugs like amphetamine or cocaine, but rather a mixture of sedatives with relatively low toxicity which are rarely fatal.…”
Section: Discussionmentioning
confidence: 99%
“…That said, there are significant difficulties related to identifying the substances accurately (as labelling of products is unreliable), and verification would likely require expensive techniques such as gas chromatography spectrometry [15]. In addition, there is a concern that some of these preparations are ‘spiked’ with alternative substances; indeed, one New Zealand study reported presence of the benzodiazepine phenazepam in preparations of K2 [35]. If this was widespread, then this may explain the relative severity of some client's withdrawal reaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, various products from Japan contained RCS-4 at concentrations of 18 and 1.7 mg/g herbal matter, suggesting limited knowledge about the potency of this compound by manufacturers [14]. The N-butyl homologue of RCS-4, RCS-4-C4 (6), was found in products purchased in New Zealand in July 2011 [19], and the regioisomeric RCS-2-C4 (4) was identified in seized products by researchers at the National Forensic Service in South Korea in October 2012 [22]. The same group also found RCS-2 (7) and RCS-3 (8) in their seizure materials until June 2013 [23].…”
Section: Introductionmentioning
confidence: 98%
“…RCS-4 has been identified in commercial products seized in the USA [16], Belgium [17], South Korea [18], and New Zealand [19], suggesting widespread use internationally. In 2011, RCS-4 was the third most common substance identified in ''herbal highs'' products obtained in Poland [20].…”
Section: Introductionmentioning
confidence: 99%